Anterior knee pain and patellar instability - Sanchis-Alfonso, Vicente (Springer London : Imprint: Springer, 2006)
Anterior knee pain and patellar instability is the most common pathology of the knee. Nevertheless, it is the most neglected, the least known and the most problematic. Our knowledge of its etiopathogeny is also limited, with the consequence that its treatment is of the most complex among the different pathologies of the knee. With contributions from orthopedic surgeons, physiotherapists, radiologists, biologists, pathologists, bioengineers, and plastic surgeons, this multidisciplinary book reviews the diagnosis and management of anterior knee pain and patellar instability in an eminently clinical and practical manner. The book reviews the therapeutic alternatives, both surgical and non-surgical, emphasizing the considerable importance of minimal intervention and non-surgical methods. Similarly, anterior knee pain following ACL reconstruction is covered in detail. Complex clinical cases are also discussed at length with the use of numerous illustrations, with each case providing the key information to assist diagnosis. Anterior Knee Pain and Patellar Instability has been written for orthopedic surgeons, specialists in sports medicine and physiotherapists and fills an important gap in the literature of pathology of the extensor mechanism of the knee. It is an authoritative reference on one of the most problematic entities current in pathology of the knee.